Continuing pedagogical staff development in engineering University; Interactive Collaborative Learning (ICL2013) - Minin M. G. Mikhail Grigoryevich; Pakanova V. S. Valentina Sergeevna; Benson G. F. Gleb Feliksovich; Belomestnova E. N. Emilia Nikolaevna (2013, 2013)
Title screen